IMPLEMENTATION OF GEOMETRIC MEAN FILTER METHOD FOR IMPROVING WITH NOISE REDUCTION IN DIGITAL IMAGE - Henri Pandiangan (Jurnal Mantik Penusa, 2018)
Image plays a very important role as a form of information. As the convenience offered in taking, processing and storing, many people are leaving analogue images and switching to digital images. Digital image is one of the easiest forms of imagery used in terms of shipping as data, image processing and processing itself. Although an image is rich in information, but often the image we have has a decrease in the quality intensity, for example contains defects or noise (noise), the color is too contrasting or blurred. Decreasing the quality intensity, usually occurs in the process of taking or storing images (digital images). Mean filter is one of the linear filtering which functions to smooth and eliminate noise in an image that works by replacing the intensity of the pixel value with the average value of the pixel with the value of neighboring pixels. The application in this study was implemented using the VB.Net.2008 programming language and the database using Mysql.